Development of Batak Weaving Tradition as a Creative Economic Product Based on Local Wisdom - Sinulingga, Jekmen; Situmorang, Rahel Theresia Rodame; Tifany; Siregar, Arjuna Junifer (Raja Zulkarnain Education Foundation, 2025)
Developing the Batak weaving tradition as part of the creative economy is a strategic effort to strengthen cultural values ​​while improving the welfare of local communities. This study aims to analyze the preservation, innovation, and utilization of local wisdom in the Batak weaving production process so that it can be developed as a competitive creative economy product. The research method used a qualitative approach using observation techniques, in-depth interviews, and documentation studies of ulos artisans in several regions in North Sumatra who still preserve Batak weaving. The results show that the weaving tradition not only functions as a socio-ritual identity and symbol but also has high economic potential when packaged innovatively. Motif development, product diversification, and the use of natural dyes are key strategies to meet the needs of the modern market without abandoning traditional values. Furthermore, the role of indigenous communities and women weaver groups is crucial in maintaining the continuity of local knowledge. The main challenges faced are limited regeneration of young weavers, a lack of support for production technology, and limited market access. This study confirms that the integration of local wisdom, design innovation, and digital marketing strategies can strengthen the position of Batak weaving as a competitive creative economy product. Thus, developing the weaving tradition is not only a means of cultural preservation but also a path to sustainable economic empowerment for the Batak people.